The Evaluation Of Potasium Thiocyanate Extracted Pasteurella multocida Vaccine On Pig - E.S. Pribadi; C.S.U. Pramono; M.B.M. Malole (Media Veteriner, 1996)
Pasteurella multocida has been isolated from pigs at Kapuk Farm West Jakarta that had been diagnosed pasteurellosis. These isolates were extracted with potassium thiocyanate(KSCN) and has been evaluated as vaccine for pig. Seventeenth 3-4 years-old pigs were used for experiment and they were divided to four groups. i.e (i) control, (ii) vaccination, (iii)vaccination and challenge and (iv) challenge groups. All pigs were fed and receive water ad Irbiturri. The experiment was carried out for 30 days. All experiment groups showed no difference statistically for antibody titer until days-21. At days-23, vaccination groups showed antibody titer higher than non vaccination groups.Challenge groups showed clinical sign i.e. anorexia, abdominal respiration, rhinitis and demonstrated pathological changes i.e. local dermatitis superficialis, limphadenitis, oedem cervicalis ventral, trcheitis, laryngitis, pleuropneumoni, emphysema pulmonum, pleuritis, pericarditis, epicarditis, hipertrophy ventricle dextra, dilatation ventricle sinistra, splenitis, anteritis catarhalis, tephlitis, colitis, cystitis,, myositis necroticans, gastritis catarhalis and gangrenosa, degeneration parenchymatosa. hidronephrosis, sinusitis catarhalis,pneumoni lobuler and epiglositis. Histopathological changes showed alveoli damaged, germinal ccnters formation in spleen and timpltoglandulae which was more severe in thechallenge groups. P. multocida was isolated from visceral organs that showed pathology and histopathology changes.Mild clinical signs was observed in the vaccination groups. This groups showed similar pathological changes as other groups but therc were no d e m a at cervicalis region. This group showed chronic histopathological changes. No P. nrultocido was isolated from visceral organs. It can be concluded that all vaccinated pigs was protected by vaccine during the 30days experiment.